ETNOMATHEMATICS: EXPLORATION OF THE ART OF KENTHONGAN MUSIC AS A SOURCE OF MATHEMATICS LEARNING - Fitria Zana Kumala; Zaenurrohman Zaenurrohman; Nurul Ma’unah; Gunawan Gunawan (Yayasan Education and Social Center, 2022)
Ethnomathematics is an approach tio learning mathematics that connects the material studied with the local culture of students. Ethnomathematics can be used by mathematics educators to overcome problems in the field of mathematics, namely the negative perception of students about mathematics which is seen as difficult. This study aims to explore, identify, describe and analyze mathematical concepts contained in the art of kenthongan music. This research is a qualitative descriptive exploratory research with an ethnographic approach. Data were collected by observation, documentation, and interviews. This research was conducted on the kenthongan music art group